The effect of heat treatment on the anode efficiency of Magnesium sacrificial anode - A.M.H., Firdaus; Saiful Rizam, Shamsudin; Shamsul Baharin, Jamaludin; Mohd Nazree, Derman (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.